Effective Sexual Education Model For Preventing Sexual Violence in Children - Sipahutar, Ida Erni; Hartati, Ni Nyoman; Runiari, Ni Nengah; Wedri, Ni Made; Suardani, Ni Luh Ketut (South East Asia Nursing Research, 2024)
The study aimed to measure the level of knowledge of fostering family welfare mothers before and after being given sexual health education education on efforts to prevent sexual violence in children, to prove the effectiveness of developing a sexual health education model for efforts to prevent sexual violence in children. The research method uses Quasi-Experimental and the research design used is nonequivalent Control Group Design. The results of the study found that the knowledge level of respondents in the pre-test treatment group had a low knowledge level of 33 respondents (55%) and a high level of knowledge of 27 respondents (45%). The level of knowledge of respondents in the post-test treatment group with the highest level of knowledge was 44 respondents (73.3%) and 16 respondents (26.7%) had a low level of knowledge, the P-value was .001. The attitude of the respondents in the pre-test treatment group had the most with less than 60 respondents (100%) and 0 respondents (0%) having a good attitude. The attitude of the respondents in the post-test treatment group was the most lacking, 31 respondents (51.7%) and 29 respondents (48.3%) had a good attitude, and the P-value was .073. Most of the respondents in the pre-test control group had a knowledge level of 32 respondents (53.3%) and a high level of knowledge of 28 respondents (46.7%). The highest level of knowledge of respondents in the post-test control group had a high level of knowledge of 31 respondents (52.1%) and had a low level of knowledge of 29 respondents (48.8%), the P-Value was .000. The attitude of most respondents in the pre-test control group had a less attitude of 34 respondents (56.7%) and had a good attitude of 26 respondents (43.3%). Most of the respondents in the post-test control group had a good attitude of 33 respondents (55%) and had a less attitude of 27 respondents (45%), the P-Value was .000.